The inventory of local wisdom: Amanuban-Dawanese medicinal plant in Timor Tengah Selatan District - Tefu, Meti OFI; Sabat, Dian Ristiani (Universitas Negeri Jakarta, 2022)
One of the preserved local wisdom of Dawanese (Amanuban) Timor Tengah Selatan District is using plants as traditional medicine. The Dawanese (Amanuban) knowledge of using herbal plants is inherited spontaneously based on the experience and skill of the ancestors. The knowledge is inherited orally and limited to family members and siblings. This research aims to invent species of plants, the plant parts, and their functions used by Dawanese (Amanuban) as traditional medicine. This research is descriptive qualitative research with observation and structured interviews as the instruments. The informants were chosen based on Purposive Sampling using Snowball Sampling. There are 40 informants in this research. The data in this research were analysed using the descriptive qualitative analysis technique and were tabulated in tables. Based on the research result, there are 103 species of plants used by Dawanese (Amanuban) as traditional medicine. Of the 103 kinds of plants used to treat 23 groups of diseases. The way to mix the traditional medicine by Dawanese (Amanuban) varies depending on the species of plants, the parts of plant used, and the species of disease cured. The general way used by Dawanese (Amanuban) is by boiling. The novelty of this research is the disclosure of local wisdom in the use of plants owned by the Dawanese (Amanuban) people. The results of this study are expected to support the preservation of biological and cultural resources. Therefore, it is necessary to identify further the Kulit Pahit (Melicope) plants that have not been identified to the species level.